Dampak Aktifitas Merger Dan Akuisisi Kepada Biaya Hutang Pada Perusahaan Di Indonesia - Media Kusumawardani; Achmad Soediro; Fardinant Adhitama; Muhammad Farhan; Desri Yanto (Politeknik Ganesha Medan, 2022)
The research is related to the cost of debt that occurs when companies carry out merger and acquisition activities in the 2010-2018 period. The independent variable of this research is the cost of debt, the dependent variable is the revaluation of assets, the addition of new assets, and the addition of new guarantees, while the control variables are firm size, leverage, ratio of assets. The purpose of this study was to determine the impact of changes in assets on mergers and acquisitions activities carried out by the company on the cost of debt. The objects of this research are companies listed on the Indonesia Stock Exchange 2010-2018 that carry out mergers and acquisitions. Data collection method, using purposive sampling method and resulted in 62 companies that meet the requirements for research. The type of data used is secondary data. Data were analyzed using multiple regression analysis with the help of Eviews10. In this study, the revaluation of assets, the addition of new assets, and the addition of new collateral do not have a significant effect on the cost of debt. The results of other studies show that among the three control variables, firm size, the ratio of assets does not have a significant effect, while leverage shows a positive effect on the cost of debt.